KEPENTINGAN RUSIA DALAM MENGIRIMKAN PRIVATE MILITARY COMPANY (THE WAGNER) KE LIBYA TAHUN 2017-2020 - Alya Fathia Fitri; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
In the midst of the controversy over the legality of using a Private Military Company (PMC), Russia still sent PMC the Wagner as a means to pursue its foreign policy in North Africa and the Middle East, particularly Libya. Russia uses Wagner's PMC to boost advantages in reaching its military modernization goals and expand its influence to North Africa and the Middle East, where the United States and the NATO alliance also play a role in the dynamics of the geopolitical situation in the region. Russia's motivation for implementing this policy and the results were explained in this study. This study uses the rational actor approach within the theory of Foreign Policy Analysis. The method in this qualitative research uses data collection techniques in the form of books, research, official documents, reports, articles, and website publications that have relevance to the research. In analysing the research problem, the author beholds through the perspective of Neo-classical Realism in the study of international relations. The results of this study indicate that Russia sent PMC Wagner to Libya as a strategy to secure its geopolitical interests, as well as to expand its influence in North Africa and the Middle East. Russia's geopolitical interests include oil and gas mining assets inherited from the Soviet Union, which historically had good relations with Gaddafi's Libya. During the Putin administration, this strategy was revitalized by leveraging the power of PMC Wagner in collaboration with the Libyan National Army group led by Khalifa Haftar, in which this strategy influenced the rise in Russia's arms to trade regionally. Keywords: Russia, Geopolitics, Private Military Company, Foreign Policy, National Interests, Libya